2016
DOI: 10.3390/lubricants4020015
|View full text |Cite
|
Sign up to set email alerts
|

Pleural Lubrication

Abstract: During breathing, the pleural surfaces slide against each other continuously without damage. Pleural liquid and lubricating molecules should provide the lubrication of the sliding surfaces, thus protecting the mesothelium from shear-induced abrasion. D' Angelo et al. (Respir. Physiol. Neurobiol. 2004) measured the coefficient of kinetic friction (µ) of rabbit parietal pleura sliding against visceral pleura in vitro at physiological velocities and under physiological loads; it was~0.02 and did not change with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…The mean value of µ was 0.0175 ± 0.001. This value was similar to those measured on pleural tissue specimens (approximately 0.025) [19], and on mesothelial cells in vitro (0.021 ± 0.001 and 0.032 ± 0.002 in 4/4 RM-4 and CARM-L1 TG3 cell line, respectively) [13]. Chen et al [14] found that the surface sliding friction of endothelial cell monolayers cultured on soft PNaSS gel was much greater than that exerted on the walls of blood vessels in vivo.…”
Section: Discussionsupporting
confidence: 89%
“…The mean value of µ was 0.0175 ± 0.001. This value was similar to those measured on pleural tissue specimens (approximately 0.025) [19], and on mesothelial cells in vitro (0.021 ± 0.001 and 0.032 ± 0.002 in 4/4 RM-4 and CARM-L1 TG3 cell line, respectively) [13]. Chen et al [14] found that the surface sliding friction of endothelial cell monolayers cultured on soft PNaSS gel was much greater than that exerted on the walls of blood vessels in vivo.…”
Section: Discussionsupporting
confidence: 89%
“…The potential for therapeutic manipulation of these diverse functions has been complicated by the presence of a carbohydrate surface layer—here, called the mesopolysaccharide (MPS)—that coats the outer layer of the mesothelium. Although the structure and function of the MPS is not fully-understood, a common understanding is that the MPS creates a frictionless surface facilitating the movement of the ventilating lung, beating heart and peristaltic bowel [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Movement promotes HA turnover, whereas immobilization favors accumulation [13]. Mesothelial cells secrete HA which play chemo-mechanical roles favoring lubrication and water homeostasis in pleural, pericardial, and peritoneal fluids, therefore contributing to vital physiological functions [14,15].…”
Section: Ecm In Physiological Tissue Biomechanics and Adaptationmentioning
confidence: 99%